Handbuilt pottery techniques revealed the secrets of handbuilding shown in unique cutaway photography - Atkin, Jacqui (Barron's, 2013)
Atkin takes the mystery out of hand-building by showing precisely what happens at each point in the process. Simple, creative projects clearly illuminate coil, slab, molds, and pinch techniques--all demonstrated in clear step-by-step photos.